High-grade appendiceal mucinous neoplasms in children: a case report - Wang, Hongli; Zhang, Jin; Hao, Xiwei; Lu, Hongting; Li, FuJiang; Shang, Cong (Frontiers in Pediatrics, 2025)
BackgroundAppendiceal Mucinous Neoplasms (AMNs) are a rare disease characterized by the accumulation of mucus within the vermiform appendix and are frequently misdiagnosed as appendicitis. Hence, it is crucial to consider AMNs because they have the potential to progress into peritoneal pseudomyxoma (PP), a clinical syndrome distinguished by mucus buildup in the peritoneum leading to progressive abdominal pathology.Case reportWe present a case involving a 13-year-old male patient who was initially suspected of having acute purulent appendicitis prior to surgery, a formal laparoscopic appendectomy was performed. Microscopic examination revealed the presence of high-grade appendiceal mucinous neoplasm (HAMN), with certain areas exhibiting features consistent with mucinous adenocarcinoma, and focal invasion of the muscular layer was observed. After multidisciplinary discussion, the patient underwent laparoscopic ileocecal resection followed by hyperthermic intraperitoneal chemotherapy (HIPEC) and molecular targeted therapy leading to favorable outcome during subsequent regular follow-up evaluations validating the appropriateness of the chosen surgical procedure.ConclusionThis case presents a rare pediatric appendiceal mucinous tumor, highlighting the importance of recognizing the presence of a tumor for clinicians when diagnosing an appendiceal abscess.